1976
DOI: 10.1007/bf03189267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of liver disease on the elimination of drugs

Abstract: Av.ail~bl~literature contains some contradictory clinical evidence about the effect of liver disease on the metabolism a.nd elImmatIo~of~rugs. !n the ma!~rity of the cases, drugs are more slowly eliminated in patients with hepatic dysfunction, such as cirrhosis or viral hepatitis. However, there is no single biochemical liver test for the proper characterization of the functional s.tatus of the. liver. Since all drugs behave differently pharmacokinetically, no predictions can be made fr?~th~results with one pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…These results agree with those of previous studies which have shown that oxidative drug metabolism in general may be affected by hepatic cirrhosis (Klotz 1976). However, these patients with cirrhosis were older (40 to 80 years) than the healthy volunteers (19 to 31 years) which were used for comparisons.…”
supporting
confidence: 93%
“…These results agree with those of previous studies which have shown that oxidative drug metabolism in general may be affected by hepatic cirrhosis (Klotz 1976). However, these patients with cirrhosis were older (40 to 80 years) than the healthy volunteers (19 to 31 years) which were used for comparisons.…”
supporting
confidence: 93%
“…Alcohol abusers are often affected by changes * To whom correspondence should be addressed in their liver function tests and it is well known that the pharmacokinetics of drugs eliminated primarily by hepatic metabolism can change significantly in patients with liver disease (Klotz 1976). For instance, alterations in liver blood flow, intrinsic clearance and serum protein binding may result in increased steady-state plasma lcvels of such drugs administered in the usual therapeutic doses.…”
mentioning
confidence: 99%